NANOTECHNOLOGY: FINDING NEW SOLUTIONS FOR PREVENTIVE DENTISTRY - A.V. BLINOVA (Паёми Сино, 2021)
Individual oral hygiene is the key element of the complex programs, developed for prevention of caries and inflammatory periodontal diseases. The industry of care cosmetic, especially dental care cosmetic, is so sensitive to modern conceptions and scientific achievements. It tries to use them to create more effective and commercially successful products. Incorporation of nanoparticles into dental composites, disinfected solutions for irrigation of root canals, bioactive covers for titanium and zirconium implants no longer cause skepticism. Using nanoparticles in cosmetic formulations allows us to achieve high filling and active surface area, and therefore, improve cleaning and antimicrobial properties. The aim of this review is to study the promising and already existing areas for using nanotechnologies for prevention of dental disorders. First of all, we are interested in the creation of new oral hygiene products. The samples of nano-containing toothpastes, mouthwashes, mousses and adhesive films, already presented on the market, demonstrate a high remineralizing potential, and with regular use, they are apparently able to provide a prolonged bacteriostatic effect. At the same time, currently there is no information in the public science press about the general or local toxic effects, caused by these biologically active drugs.